A Systematic Literature Review of Single Subject Design Research within Foster Care. - Kelly, Sophia; Mahoney, Amanda (Behavior & Social Issues, 2025)
Foster children and families face unique circumstances including the need for continual adaptation to shifting environments and support networks. Using single-subject research logic relies on each participant serving as their own control, which, compared to group design research, can have advantages for evaluating behavioral interventions under these dynamic contexts. We examined all studies between 2010 and 2024 that employed single-subject research design to evaluate behavior analytic interventions with participants who are part of the foster care system. The literature search and classification system yielded seven articles. Nearly all interventions were found to have a medium-to-large effect size, although none of the studies met all high-quality single-subject design research standards. Most studies were deemed to have good ecological validity, but measures of social validity were commonly absent. There is a need for further research on behavioral interventions to support foster care families, particularly on parent and teacher training. We discuss the advantages of single-subject research designs and the importance of conducting socially significant research in a natural setting like home or school.